Risk and protective factors of suicidal behavior in adolescents: First Public Primary Care Survey (December 2016 - September 2017) (Archives of Pediatrics of Uruguay, 2022)
Introduction: self-harm (SH) and suicide have increased in adolescents, and they have become a high health priority.Objective: to establish the epidemiology and its relationship with risk factors (RF) and protection (PF) of suicidal behavior in users of a Primary Care Adolescent Center of the State Health Sector (December 2016 - September 2017).Materials and methods: confidential survey of adolescents of both sexes, between 12 and 19 years of age. We carried out a descriptive analysis in order to compare RF and PF between ages (12 to 14 and 15 to 19); sex; previous SH self-harm versus its absence and institutionalization or not. p less than 0.05 was considered statistically significant. Data were entered into Excel and analyzed using Epi Info 7.2.0.1.Results: 107 interviewees, 60 females, age: 13.3 (mean); Most frequent previous SH between 15 and 19 years and female sex (p
Keywords: Suicide; Depression; Adolescent; Risk factors